Kebijakan Pemerintah Kota Lhokseumawe dalam Mengatasi Ketertiban Pedagang Kaki Lima dalam Perspektif Fikih Siyasah - Kafrawi, Kafrawi; Funna, Cut Ariska (Constitutional Law and Siyasah Department, Sharia and Law Faculty, IAIN, 2022)
This study describes government policies in overcoming street vendors based on the Siyasah Jurisprudence Perspective, looking at and studying the policies of the lhokseumawe city government regarding the street vendors around the city of lhokseumawe. The type of research used is qualitative, namely research procedures that produce descriptive data. The results of the study show, (1) the policy of the Lhokseumawe city government, namely the Satpol PP Service, the policy issued by the government in perfect Fikih Siyasah is a policy that allows/allows street vendors to sell on predetermined Sukaramai roads. the goal, so that street vendors can make a living in peace and the city of Lhokseumawe looks orderly and clean (2) The obstacle faced by the government of the city of Lhokseumawe in dealing with street vendors is the lack of awareness of street vendors (PKL) selling in locations that have been banned , like not wanting to care about the order and security of the city of Lhokseumawe. Lack of understanding of street vendors about local regulations governing street vendors, as well as relevant local regulations.